Ryzyko w ocenie efektywności elektroenergetycznych inwestycji sieciowych na przykładzie wybranych inwestycji - Wasiuk, Małgorzata (Risk in Effectiveness Assessment of Energetic Investment Based on Selected Investments, 2005)
The economic effectiveness of investment decision we can evaluate on the basis of NPV. Effectiveness assessment concerns future effects, which are based on estimated incomes and expenses (during 10- 25 years). Indexes calculated for simulated future effects are burden with suspense, it involves risk that effects will be different that expectations. In this paper the results of risk assessment researches as one of the element of whole planning investment were presented. The molding of distribution of NPV index was carried out by means of Monte Carlo method. The parameters of the distribution were also estimated. The relationships between NPV index and extreme values of individual distribution were described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 653-662